Hubungan Intensitas Penggunaan Gadget dengan Perkembangan Anak Usia 4-6 Tahun - Kusuma, Anggi; Yunitasari, Eva; Sugiyanto, Sugiyanto; Anggraini, Reni; Mukhlis, Hamid (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
As many as 88.3% of children under five in Indonesia experience developmental disorders. One of the factors that affect children's social development is the child's habit of playing with gadgets. The aim of this research is to know the relationship between the intensity of gadget usage and with the growth of children ages 4-6 years old at Masjid Agung kindergarten, Kalianda, Lampung Province. Kind of this research is quantitative research, research design is using correlative analytical with cross-sectional approaches. The population that was used are all students of class A, B, and C the numbers of students are 85 students. The sampling method that is used is consecutive sampling, The sample size is 44 students, which is children aged between 4-6 years old at Masjid Agung kindergarten, Kalianda, South lampung. bivariate analysis using the Chi-Square test. The research results obtained a value, of P-0,001, which means there are relationships that significantly between using gadgets and the growth of children at Masjid Agung Kindergarten, Kalianda. This research is expected as a material reference that gives literature source value and beginning data of doing next research and the teachers at the school could stimulate the pupils on their growth appropriate the ages and the parents could limiting permission of playing gadget. Abstrack: Sebanyak 88,3 % balita di Indonesia mengalami gangguan perkembangan Salah satu faktor yang mempengaruhi perkembangan sosial anak yaitu kebiasaan anak dalam bermain gadget.Tujuan penelitian ini adalah untuk mengetahui hubungan intensitas penggunaan Gadget dengan perkembangan anak usia 4-6 tahun di TK Masjid Agung Kalianda.Jenis Penelitian adalah kuantitatif, desain penelitian menggunakan metode analitik korelasi Dengan pendekatan cross-sectinal, Populasi yang digunakan adalah semua siswa kelas A,B dan C yang berjumlah 85 siswa. Metode sampling yang digunakan adalah concecutive sampling Besar sampel yaitu berjumlah 44 siswa, anak usia 4-6 tahun di TK Masjid Agung Kalianda.  Analisa bivariat dengan menggunakan uji Chi Square.Hasil penelitian diperoleh nilai p= 0,001, artinya terdapat hubungan yang signifikan antara intensitas penggunaan gadget dengan perkembangan anak di TK Masjid Agung Kalianda. Penelitian ini  diharapkan sebagai bahan referensi memberikan nilai sumber kepustakaan dan data awal dalam melakukan penelitian selanjutnya serta  guru di sekolah dapat menstimulasi anak didiknya dalam perkembangan sesuai usia, orang tua juga agar membatasi pemberian bermain gadget.